THE ROLE OF HUMANISM IN THE DEVELOPMENT OF THE INDEPENDENT CURRICULUM BASED ON CHARACTER EDUCATION IN INDONESIA - Maksum; Khasanah, Nur (Jurnal Ilmu Pendidikan Indonesia, 2026)
This study discusses how the humanistic approach contributes to the development of character-based education curricula in Indonesia, particularly in the implementation of the Merdeka Curriculum. This curriculum represents a reform of the national education system that focuses on strengthening competencies and character building to realize the Profile of Pancasila Students. The study employs a literature review method with a descriptive qualitative approach, by analyzing various written sources related to humanistic theory, character education, and the Merdeka Curriculum policy. The findings indicate that humanistic education places students at the center of the learning process, aiming to help them recognize and develop their potential holistically intellectually, emotionally, socially, and spiritually. These humanistic values align with Ki Hajar Dewantara’s philosophy, which emphasizes freedom and the cultivation of noble character in education. In practice, humanistic values are reflected through student-centered learning, the teacher’s role as a facilitator, and the Project to Strengthen the Profile of Pancasila Students (P5), which fosters cooperation, independence, and tolerance. However, the implementation of humanistic education still faces several challenges, such as limited teacher understanding, rigid school culture, and assessment systems that focus primarily on academic outcomes. Therefore, teacher training, policy support, and collaboration among schools, families, and the government are needed to optimally apply humanistic values. Through this approach, education is expected to produce Indonesian generations who are faithful, virtuous, and ready to face the challenges of the modern era.